Portuguese foreign policy and crisis diplomacy in a period of German hegemony: Bandwagoning or soft balancing? - Reis, B. C. (Portugal since the 2008 economic crisis: Resilience and change, 2023)
The global financial crisis, followed by the European debt crisis, had a negative effect on several economically vulnerable countries in the periphery of the eurozone, including Portugal. This chapter seeks to contribute to the ongoing debate about its impact on the balance of power in Europe and, in particular, in the European Union (EU). The central question of this chapter is whether the major external shock of 2008 led to a major change in Portuguese foreign policy priorities and whether this fits into a pattern of growing German hegemony in Europe. The answer is a qualified ‘yes’. My argument is that the main impact of this major economic crisis was to make economic diplomacy and Germany more central in Portuguese foreign policy. But an important divergence emerged regarding what to do diplomatically about Germany: to bandwagon or to soft balance? Bandwagoning prevailed in the initial stages of the crisis when the difficulties were more acute, and a right-wing Portuguese government was ideologically more aligned with the same objectives as the German government, namely in terms of austerity and budget discipline. Soft balancing - looking for allies to resist German pressure and aims, first and foremost France, without antagonizing the latter too openly - was the preferred option for a more left-wing government aiming at more flexible, less austerity-centric policies in a more favourable economic and European context, culminating in the election of minister of finance Mário Centeno as the president of the Eurogroup in December 2017. This argument will be sustained by analysing party and government manifestos, official documents and interviews. While my main focus will be on the period up to the end of 2017, I will bring my analysis to the present day by arguing that Brexit, the election of a German president of the EU Commission and the outbreak of the COVID-19 pandemic seemed to confirm and reinforce the hegemonic role of Germany, even if the symmetric shock brought about by the pandemic led to a major change in German posture. The very adverse implications of the Russian Federation’s military invasion of Ukraine, in February 2022, for German credibility and dominance will be briefly mentioned.